Functional significance of a C→A polymorphism in intron 1 of the cytochrome P450 CYP1A2 gene tested with caffeine - Sachse, Christoph (Blackwell Science Inc, 1999)
AIMS: The cytochrome P450 enzyme CYP1A2 metabolises several drugs and carcinogens. We wanted to determine how much of the variability of CYP1A2 activity is explained by a newly discovered gene polymorphism in intron 1. METHODS: A single nucleotide polymorphism in intron 1 of the CYP1A2 gene at position 734 downstream of the first transcribed nucleotide was identified by DNA sequence analysis. The functional significance of this C/A polymorphism was assessed in 185 healthy Caucasian non-smokers and in 51 smokers by genotyping and phenotyping using caffeine (100 mg oral dose). RESULTS: Out of the total sample, 46% were homozygous for the variant A, 44% were heterozygous, and 10% were homozygous for the variant C. The ratio of 1,7-dimethylxanthine (17X) plus 1,7-dimethyluric acid divided by caffeine in 0–5 h urine samples from 185 non-smokers did not differ significantly between the three CYP1A2 genotypes. In the 51 smokers, analysis of variance revealed significant differences in the 5 h plasma 17X/caffeine ratios between the genotypes (P=0.008, F-test). The mean ratio was 1.37 in carriers of the A/A genotype, 0.88 in heterozygotes and 0.82 in carriers of C/C. The mean difference between the A/A and C/A groups was 0.48 (95% confidence interval 0.15–0.81; P=0.01). CONCLUSIONS: The A/A genotype, which may represent a CYP1A2 high inducibility genotype, may either be a direct cause of increased CYP1A2activity, or be genetically linked to polymorphisms conferring high inducibility. Further studies are needed to define the role of this polymorphism on the pharmacokinetics of drugs metabolised by CYP1A2 and in the activation of carcinogens.